2004
DOI: 10.1007/s00468-003-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Studies of crystallinity of Scots pine and Norway spruce cellulose

Abstract: The variation in the mass fraction of crystalline cellulose (crystallinity of wood), the intrinsic crystallinity of cellulose, and the thickness of cellulose crystallites in early wood of Norway spruce [Picea abies (L.) Karst.], and Scots pine (Pinus sylvestris L.) grown in Finland were studied using wide angle X-ray scattering and nuclear magnetic resonance spectroscopy. The mass fraction of crystalline cellulose in wood increased slightly with the distance from the pith and was about 30€4% in mature wood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 41 publications
11
63
0
6
Order By: Relevance
“…For example, softwood species contain cellulose of 52 to 62% crystallinity (1,24) and the value for switchgrass is 55% (12), which compares with a value of 65% for poplar (38). This higher value is close to the range (66 to 75%) for the form of cellulose (Avicel) (18) used as a model substrate in the growth studies reported here.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, softwood species contain cellulose of 52 to 62% crystallinity (1,24) and the value for switchgrass is 55% (12), which compares with a value of 65% for poplar (38). This higher value is close to the range (66 to 75%) for the form of cellulose (Avicel) (18) used as a model substrate in the growth studies reported here.…”
Section: Discussionmentioning
confidence: 59%
“…Not many microorganisms are able to degrade pure crystalline cellulose, and the cellulose in plant biomass has a high order of crystallinity and is even less accessible to microbial or enzymatic attack (1,(12)(13)(14). Aerobic cellulolytic microorganisms usually secrete (hemi)cellulolytic enzymes containing carbohydrate-binding modules that serve to bind the catalytic domains to insoluble substrates.…”
mentioning
confidence: 99%
“…2) MCC was partially crystalline cellulose I, with a large thickness of crystallites, B 200 = 7.4±0.1 nm. For comparison, for commercial microcrystalline cellulose, Avicel, the thickness of crystallites B 200 is 4.7 nm [31]. By comparing XRD results for the pure MCC and the MCC-Cu nanocomposites it was concluded that the nanoparticle formation did not affect the semi-crystalline structure of MCC.…”
Section: Resultsmentioning
confidence: 99%
“…17 The relative crystallinity was determined by fitting the amorphous background and the theoretical intensity of crystalline cellulose to the experimental diffraction pattern. 17 The accuracy was ±5 %.…”
Section: Wide Angle X-ray Scatteringmentioning
confidence: 99%